Estudo da aderência aço-concreto sob a influência da reação expansiva no concreto produzido com areia de minério de ferro - Hounga, Sègbégnon Hubert (2024)
The deterioration of reinforced concrete structures due to expansive reactions can be numerous and varied. This study experimentally analyzed the bond behavior between steel and concrete produced with residue sand, which is a byproduct of mining, when subjected to expansive reactions. The analysis was conducted using the pull-out test, which consists of applying an axial tensile load to evaluate the bond between the steel and the concrete. To this end, different test specimens were produced with 65% replacement of natural sand by iron ore tailings sand, varying the parameters of the concrete (30 and 60 MPa) and the steel (6.3, 8.0, 10.0, and 12.5 mm). These samples were subjected to three levels of expansion (0.00%, 0.05%, and 0.30%) due to delayed ettringite formation (DEF), allowing for a more comprehensive analysis of the effects of expansive reaction on the steel-concrete bond. Measurements indicated that the 0.05% level occurred in C60 concrete thermally treated at 85°C after 130 days of storage at 100% relative humidity. The concrete showed a gain in compressive strength of about 3 MPa with this level of expansion. The results indicate that, despite the high utilization of this sand in the concrete mix, the bond behavior did not change, regardless of the bar diameter. Compared to the values found in the literature, the specimens showed higher bond strength, mainly due to the improved bond interface resulting from the hydration reaction with the used replacement content.